A permanent wireless dynamic monitoring system for the Colosseum in Rome. Issue 2 (3rd April 2018) - Monti, Giorgio; Fumagalli, Fabio; Quaranta, Giuseppe; Sgroi, Marco; Tommasi, Marcello
Abstract: The protection of historical monuments from road and subway traffic vibrations is an important responsibility for the administrations of many cities. The structural health of monuments is threatened both by the effects of short-term vibrations due to construction activities and by the consequences of long-term vibrations induced by vehicles and subways. The most important historical constructions are often endowed with monitoring systems to measure and analyze these effects. A state-of-the-art monitoring system has been developed and deployed for the continuous "trigger-free" dynamic monitoring of the Flavian Amphitheater, known as the Colosseum, in Rome, Italy. A new subway line will pass nearby the foundations and there is serious concern that the Monument be damaged. The monitoring system is composed of wireless accelerometers located on the top portion of the North façade of the Monument and has allowed to study the recorded vibrations. The system architecture, the wireless protocol and the data processing are described in detail in this paper. A discussion on the data collected during two years of monitoring is presented, with focus on statistical representations of the dynamic response, which are meaningful and synthetic indicators of the effects induced on the Monument by external actions of both natural and man-made nature.